2020
DOI: 10.1088/1361-6420/ab67dc
|View full text |Cite
|
Sign up to set email alerts
|

On the two-step estimation of the cross-power spectrum for dynamical linear inverse problems

Abstract: We consider the problem of reconstructing the cross-power spectrum of an unobservable multivariate stochatic process from indirect measurements of a second multivariate stochastic process, related to the first one through a linear operator. In the two-step approach, one would first compute a regularized reconstruction of the unobservable signal, and then compute an estimate of its cross-power spectrum from the regularized solution. We investigate whether the optimal regularization parameter for reconstruction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 47 publications
7
15
0
Order By: Relevance
“…In fact, in [26] the authors used numerical simulations to compare the parameter that provides the best estimate of the power spectrum with the one that provides the best estimate of coherence and showed that the latter is in general two orders of magnitude smaller than the former. More recently, Vallarino et al [27] addressed an analogous problem via analytical computations, considering a simplified model. Specifically, under the assumption that the neural time series are realizations of white Gaussian processes, the authors proved that the parameter providing the best neural activity estimate is more than twice as large as the one providing the best estimate of the cross-power spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in [26] the authors used numerical simulations to compare the parameter that provides the best estimate of the power spectrum with the one that provides the best estimate of coherence and showed that the latter is in general two orders of magnitude smaller than the former. More recently, Vallarino et al [27] addressed an analogous problem via analytical computations, considering a simplified model. Specifically, under the assumption that the neural time series are realizations of white Gaussian processes, the authors proved that the parameter providing the best neural activity estimate is more than twice as large as the one providing the best estimate of the cross-power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…, which corresponds to the optimal value of λ x in the case of white Gaussian signals [27]. The blue box in Figure 3 describes the inverse procedure to obtain an estimate of the cross-power spectrum and stresses the role of the regularization parameter in the two-step process.…”
mentioning
confidence: 99%
“…It is therefore not advised to use regularization-levels that have been optimized for the estimation of source power instead of source interactions. For [35] have demonstrated that the optimal regularization-level for interactions is lower than that for source-power, at least for the ridge inverse operator (see also [36]). Fig 4 also shows that for all three estimators and for all regularization-levels, suppression levels decrease with increasing interaction lag ϕ.…”
Section: Effectivenessmentioning
confidence: 99%
“…Thus, in [35] it was observed that estimation of brain interactions from MEG data requires less strong regularization than the reconstruction of the activity time-courses. In [36] this observation is formally investigated. Selection of the optimal rank of the projection operators remains an open question that can potentially yield interaction estimators with less bias and more powerful statistical hypothesis tests.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…In order to analyze the distribution of noise energy from the levitation gap sensor across frequency domains, it can use Eq. (17) to get the power spectrum [36] of the gap sensor signal.…”
Section: B Effect Of Signal Noise From the Gap Sensor On The Levitatmentioning
confidence: 99%